THE INFLUENCE OF STUDENTS’ VIDEO PRODUCTION ON SPEAKING ABILITY (A Study based on Subak Cultural Landscape) - Putu Erwin Angga Pratiwi; I Nengah Astawa; Dewa Gede Agung Gana Kumara; Dewa Gede Bambang Erawan (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2020)
This present study used a pre-experimental one group pretest-posttest design in which either a single group or multiple groups were observed subsequently to some agent or treatment presumed to give change. The undertaking research was mainly intended to find out whether or not students’ video production based on Subak Cultural Landscape influenced the speaking ability at the eighth grade students of SMP Negeri 3 Tampaksiring. The students were required to make some groups consisting of 8-9 students and produced their own video related to a material taken from Subak Cultural Landscape text book. Meanwhile, the instruments used by the researcher were tests and questionnaire. After obtaining all the required data then the researcher used matched t-test formula to analyze the data. The result of the data analysis showed that, the mean score of pre-test was 43.22 and the mean score of post-test was 51.11. Based on the data calculation, the t-observed was higher than the t-table; therefore, the hypothesis of the study was accepted which meant there was a significant influence of students’ video production on speaking ability of the eighth grade students of SMP Negeri 3 Tampaksiring.